Early mortality after neonatal surgery: analysis of risk factors in an optimized health care system for the surgical newborn - Dora Catré; Maria Francelina Lopes; Angel Madrigal; Bárbara Oliveiros; Joaquim Silva Viana; António Silvério Cabrita (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
OBJECTIVE: Anesthetic and operative interventions in neonates remain hazardous procedures, given the vulnerability of the patients in this pediatric population. The aim was to determine the preoperative and intraoperative factors associated with 30-day post-operative mortality and describe mortality outcomes following neonatal surgery under general anesthesia in our center. METHODS: Infants less than 28 days of age who underwent general anesthesia for surgery during an 11-year period (2000 - 2010) in our tertiary care pediatric center were retrospectively identified using the pediatric intensive care unit database. Multiple logistic regression was used to identify independent preoperative and intraoperative factors associated with 30-day post-operative mortality. RESULTS: Of the 437 infants in the study (median gestational age at birth 37 weeks, median birth weight 2,760 grams), 28 (6.4%) patients died before hospital discharge. Of these, 22 patients died within the first post-operative month. Logistic regression analysis showed increased odds of 30-day post-operative mortality among patients who presented American Society of Anesthesiologists physical status (ASA) score 3 or above (odds ratio 19.268; 95%CI 2.523 - 147.132) and surgery for necrotizing enterocolitis/gastrointestinal perforation (OR 5.291; 95%CI 1.962 - 14.266), compared to those who did not. CONCLUSION: The overall in-hospital mortality of 6.4% is within the prevalence reported for developed countries. Establishing ASA score 3 or above and necrotizing enterocolitis/gastrointestinal perforation as independent risk factors for early mortality in neonatal surgery may help clinicians to more adequately manage this high risk population.